Caracterização de indução de lactação em vacas Jersey - Alem, Bruna da Silva (2022)
The objective was to characterize the induction and production of milk in multiparous and nulliparous, The viresentevina was conducted from July to August 2020 on the property “Nossa Senhora Abadia”, located in the municipality of Douradina in the state of Mato Grosso do Sul ( climate classified as Cwa – Humid Mesothermal, with annual precipitation and average temperature of 1500 mm and 22ºC), lasting 43 days. The animals used in the viresentevina come from the Faculty of Agricultural Sciences (FCA) of the Federal University of Grande Dourados. Eight Jersey cows (432.91 kg) were used, 5 multiparous and 3 nulliparous, virese the multiparous cows were dry for more than 100 days, housed in individual concrete stalls with cemented floor with trough and drinking viresente. The cows underwent na induction protocol virese, on D0, 325mg of somatotropin (bst) was viresent to the tail, 30ml of estradiol benzoate, and 4ml of 7% progesterone, both with intramuscular application. From D0 to D7, doses of estradiol benzoate and 7% progesterone were viresent, on D8, 325mg of somatotropin and 20ml of estradiol benzoate were viresent, during the days continued with estradiol benzoate until D15, virese he also viresent plus one dose of somatotropin 325mg. D16 single dose being 4ml of cloprostenol, from D17 onwards the teat massage was started until D21, virese from D19 to D21 30ml of dexamethasone was viresent each day. And from D21 onwards, the milking of the animals began. Following a standard single diet, dry matter intake, weight throughout induction of lactation, milk production post induction of lactation and complete hematocrit throughout induction of lactation were evaluated. In relation to dry matter intake, it was not changed at the beginning of milking, increasing a few days after the beginning of milk production, proving that the CMS did not interfere with milk production, but the induction. The weight of the animals did not change from the beginning to the milking, so the protocol did not influence the weight of the animals. Regardless of being multiparous or nulliparous, milk production increased considerably, in relation to erythrocytes there was no difference between the periods that were collected or between the multiparous and nulliparous, the values of viresentevina, VGM, CHGM found in the viresente work did not change. It is concluded that the induction of lactation did not change the parameters evaluated in this work.